Perilaku Konsumen dalam Pengambilan Keputusan Pembelian pada URBN Kopi oleh Masyarakat di Surabaya - Ervina Maulidina Hidayati; Merlinda Sayidatina Aisyah Putri; Lailla Nabiilah; Saifuddin Zuhri (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
URBN Kopi is one of the mobile coffee brands strategically located in front of the UPN Veteran Jatim campus, making it the main choice for students to enjoy coffee. This study identified three main factors that influence purchasing decisions, namely location, price, and product completeness. This study was conducted using an in-depth interview method with five informants consisting of active students at UPN “Veteran” Jatim. The findings of this study indicate that a strategic location in front of the campus is the main factor that facilitates student access to buy coffee, while affordable prices are an important consideration because they are in accordance with students' budgets. In addition, the completeness of the products offered by URBN Kopi also increases consumer interest in choosing this product. Based on these findings, it can be concluded that the combination of a strategic location and affordable prices play an important role in purchasing decisions, which in turn has the potential to increase consumer loyalty and repurchase interest among students.